Total Synthesis of Quercitols: (+)-allo-, (–)-proto-, (+)-talo-, (–)-gala-, (+)-gala-, neo-, and (–)-epi-Quercitol - Aucktor, Johannes; Brückner, Reinhard (Synlett, 2015)
The cyclohexenenones exo- and endo-2 were converted into the cyclohexenyl acetates exo- and endo-3 and exo- and endo-5 with a diastereoselectivity of >99:1 (2 steps). Ether cleavage with DDQ in CH2Cl2/H2O (20:1) and in situ ketal hydrolysis afforded the cyclohexenones 6 and 7 in up to 83% and 87% yield, respectively. Compound 6 was converted into (+)-allo- and (–)-proto-quercitol with a diastereoselectivity of 100:0 (4 steps). Moreover, 6 was carried on to (–)-talo-quercitol whereas 7 furnished the four remaining title quercitols (3–5 steps) including both enantiomers of gala-quercitol.
Keywords: cyclohexenones; diastereoselectivity; ether cleavage; α-hydroxy ketone; oxidation; reduction